PENGARUH KNOWLEDGE MANAGEMENT DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN CV.MULTI FUNGSI PRATAMA LUBUK PAKAM - Azhar Apriandi (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
In the face of the globalization era and also the era of ASEAN Economic Community need to continue to improve, among others in improving the performance of its employees. This can be achieved if the company focuses on improving knowledge management, the skills of its employees as well as the creation of good attitudes among its employees so that they work with high performance, quality, and with Large quantities of work. This will lead to the advancement of the company. The purpose of this research is to know the influence of knowledge management and organizational commitment to employee performance. The number of samples in this study amounted to 109 people using slovin techniques. The analytical techniques used are multiple linear regression. The results showed that simultaneous knowledge management variables and organizational commitments have significant effect on employee performance. Knowledge management variables have significant effect on employee performance and organizational commitment variables have no significant effect on employee performance.